User Experience Analysis of The Information System MBKM FKIP Muhammadiyah University Kendari - Rillan, Yasset; Razilu, Zila; Nelva Saputra, Hendra (At- Ta'lim : Jurnal Pendidikan, 2025)
This study aims to analyze the user experience of Merdeka Belajar Kampus Merdeka (MBKM) information system at the Faculty of Teacher Training and Education (FKIP), Universitas Muhammadiyah Kendari. A survey was conducted with 40 students participating in the MBKM program to evaluate ease of use, system stability, information completeness, and overall satisfaction with the system. The results showed that most users were satisfied with the system. Users rated aspects such as feature completeness, ease of navigation, and speed in uploading and downloading documents positively. Nevertheless, some areas require improvement, especially regarding user independence in completing tasks and the clarity of the interface to facilitate understanding. Overall, this study concludes that the MBKM system at FKIP Universitas Muhammadiyah Kendari has successfully met users' needs in supporting academic activities. However, improvements in several aspects are expected to improve the quality of user experience.